Appropriate technology and productivity differences: two models based based on differences in skill endowments - Dinç, Tuna Abdullah (My University, 2008)
Ülkeler arasındaki gelir farklılıklarının nedenlerini araştırmak, ekonomi biliminin en ilginç, en önemli ve çok yönlü araştırma alanlarından birini oluşturmaktadır. Konu üzerine yapılan araştırmalar teknolojik bilgi düzeylerindeki farklılıkların, bir çok örnekte söz konusu gelir farklılıklarının ana nedeni olduğunu ortaya koymaktadır. İlgili literatürün bir kolu bu durumun ülkeler arasında en gelişmiş teknolojiye erişimdeki farklılıklardan kaynaklandığını öne sürerken, diğeri söz konusu teknolojilerin gelişmekte olan ülkelerin ihtiyaçlarına uygunluğundaki farklılıkların önemini vurgulamaktadır. Bu tezde, tüm ülkelerin aynı teknolojilere erişebildikleri ve tamamen kendi gereksinimlerine uygun teknolojileri kullanabilmelerine karşın, ülkeler arasında verimlilik farklılıklarının meydana gelebileceğini tartışmaktayız. Bu çerçevede, ülkelerin teknoloji seçimlerinin faktör donatımları tarafından belirlendiği iki model ortaya koymaktayız. İlk modelde, teknolojinin durumu dışsal olarak ele alınırken, diğer modelde teknolojinin yaparak öğrenme (learning-by doing) yoluyla ilerlediği varsayılmaktadır. Her iki modelin ortak noktası nitelikli ve niteliksiz emek arzlarındaki göreli farklılıkların, ülkeler arasındaki verimlilik farklılıklarının temel nedenini oluşturmasıdır. Uygun teknoloji, Teknoloji Seçimi, Verimlilik, Nitelikli/ Niteliksiz Emek

The sources of income differences across countries are some of the most interesting, important and versatile research field in the science of economics. The works on the topic suggest that differences in technological knowledge in many cases are the main source of these income differences. One branch of the literature proposes that this is because of countries’ differential access to the most advanced technologies, while the other stresses the importance of differences in the appropriateness of these technologies to the developing countries’ needs. In this thesis, we argue that even when all countries have access to common technology frontier and can use the technologies which are fully appropriate to their needs, there will still be productivity differences across countries. To illustrate this idea, we construct two models in which countries’ choices of technology are determined by the factor endowments. In the first model, the technology frontier is taken as exogenous while in the other it is assumed that the level of technology advances by the well-known learning-by doing effect. What these two models possess in common is the view that differences in the relative supply of skilled and unskilled labor are the main source of the cross country productivity differences. Appropriate Technology, Technology Selection, Productivity, Skilled/ Unskilled Labor
Keywords: Ekonomi; Teknoloji Seçimi; Verimlilik